¿Cómo impactará la tecnología al Derecho Comercial? - Morales Cáceres, Alejandro Rafael (2020)
In a world where technology is advancing at an accelerated pace and businesses are beginning to implement it, we jurists must ask ourselves how this impacts Commercial Law and if it is necessary to create laws that promote or restrict its use. Also, it is questionable whether these new technologies will impact the societal structures that we currently know.